Public Expenditure Under Uncertainty: The Net-Benefit Criteria - Graham, Daniel A. (American Economic Review, 1992)
Public expenditure under uncertainty is modeled as the problem of determining the quantities of l public goods and m private goods to be provided to n consumers when the private goods are claims to a single commodity, "dollars," which are contingent upon the occurrence of one of m possible states of nature. A real-valued "net benefit function" is identified, and criteria based upon this function are provided which are both necessary and sufficient for Pareto-improving or Pareto-efficient solutions to this problem.